Gold Nanoparticles in Cancer Theranostics - Gao, Qinyue; Zhang, Jingjing; Gao, Jie; Zhang, Zhengyang; Zhu, Haitao; Wang, Dongqing (Frontiers in Bioengineering and Biotechnology, 2021)
Conventional cancer treatments, such as surgical resection, radiotherapy and chemotherapy, have achieved significant progress in cancer therapy. Nevertheless, some limitations (such as toxic side effects) are still existing for conventional therapies, which motivates efforts towards developing novel theranostics avenues. Owning many merits such as easy surface modification, unique optical properties and high biocompatibility, gold nanoparticles (AuNPs, GNPs) have been engineered to serve as targeted delivery vehicles, molecular probe, sensors and so on. Their small size and surface characteristics enable them to extravasate and access the tumor microenvironment (TME), which is a promising solution to realize high effective treatments. Moreover, stimuli-responsive properties (respond to hypoxia and acidic pH) of nanoparticles to TME enable GNPs unrivalled control for effective transport of therapeutic cargos. In this review article, we primarily introduce the basic properties of GNPs, further discuss the recent progress in gold nanoparticles for cancer theranostics, with an additional concern about tumor microenvironment stimuli-responsive studies.